Плазменные теплоотражающие покрытия; Известия вузов. Физика; Т. 54, № 11/2 - Асаинов О. Х. Олег Хайдарович; Баинов Д. Д. Даши Дамбаевич; Кривобоков В. П. Валерий Павлович; Михайлов М. Н.; Пащенко О. В. Олег Валентинович; Юдаков С. В. Сергей Владимирович; Чернятина А. А. (2011, 2011)
Заглавие с экрана